Concatenated RS-convolutional codes for ultrawideband multiband-OFDM - Nyirongo, N; Malik, W; Edwards, D; IEEE (2006)
In this paper, we investigate the performance of concatenated Reed Solomon and convolutional (RS-convolutional) codes for ultrawideband (UWB) multiband orthogonal frequency division multiplexing (MB-OFDM) systems. We show that RS-convolutional codes perform better than single codes at high energy-per-bit to noise ratio (Eb/N0). We also show that using a bit interleaver between the two concatenated codes degrades the system performance. Our simulations indicate that 10-bit and 11-bit RS-convolutional codes outperform single codes at high Eb/N0, with gains of more than 4 dB. We further demonstrate that 11-bit RS-convolutional codes outperform turbo codes at high Eb/N0 by more than 2 dB in various UWB channels. © 2006 IEEE.